Some novel aspects of nanocrystalline diamond nucleation and growth by direct current plasma assisted chemical vapor deposition - Lee, Hak-Joo; Li, H.; Jeon, Hyeongtag; Lee, Wook-Seong (ELSEVIER SCIENCE SA, 2010)
Some novel aspects of nanocrystalline diamond (NCD) film nucleation and growth by DC-PACVD were investigated, which focused on the effect of methane injection timing at ramp stage (see discussion in the text) and cathode temperature as well. NCD films were deposited for 4 h on a 4 in. Si wafer which was ultrasonically seeded in a methanol slurry of diamond powder with a 5 nm average diameter. The H-2/CH4/N-2 gas mixture with a composition of 96.7%/3%/0.3% was used as precursor gas. The total gas flow rate and chamber pressure were 150 sccm and 150 Torr, respectively. Discharge voltage and current of 500 V and 45 A were used respectively at a substrate temperature of 800 C. The nucleation density, microstructure, growth rate and crystallinity of the obtained NCD films were characterized by SEM, XRD, NEXAFS and Raman spectroscopy. The nucleation density was found to be sensitive to methane injection timing in the ramp stage. In addition, the cathode temperature greatly affected the nucleation density, grain size and growth rate. (C) 2010 Elsevier B.V. All rights reserved.